Strategi Guru dalam Menerapkan Model Problem Based Learning ( PBL ) Kelas 6 di SDN 02 Tanjung Balit Kabupaten Lima Puluh Kota - Putri Aprilia Susanti; Rili Anggun Wulandari; Aura Fitri Mafpirah Agus; Yarisda Ningsih; Nur Azmi Alwi (Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Critical thinking skills and student-centered learning are primary focuses in elementary education to enhance learning quality. Problem-Based Learning (PBL) is one learning model that can meet these needs. The PBL model encourages students to participate more actively in the learning process by solving everyday life problems. The purpose of this research is to provide an explanation of the methods used by teachers to implement the problem-based learning model in grade 6 of SDN 02 Tanjung Balit, Lima Puluh Kota Regency. It also aims to identify the problems faced by teachers and how the implementation of this model impacts student engagement and understanding. In this research, a qualitative case study method was used. Data were collected through in-depth interviews with the sixth-grade teacher, observations of learning activities, and documentation of learning tools and student work. The main focus of this research is how teachers use the PBL model, particularly in mathematics learning, to design, implement, and evaluate learning. The research results indicate that teachers use various strategies in implementing PBL. These strategies include identifying contextual learning problems, preparing learning plans based on PBL steps, providing relevant teaching materials and student worksheets, and assessing student work processes and outcomes. Teachers also face several challenges in implementing PBL, such as a lack of student participation in group discussions and limitations in students' critical thinking skills at the initial stage. Nevertheless, the implementation of the PBL model has proven to increase student engagement in the learning process and help them understand the material better. Thus, the teacher's strategies in managing the stages of PBL are an important factor in the successful implementation of this model at the elementary school level.